The Influence Of Reciprocal Teaching Style, Exercises And Command On The Learning Outcomes Of Pencak Silat Tepak Paleredan - Veramyta Maria Martha Flora Babang; Maria Andriani Barek Ladjar; Lukas Maria Boleng (UNIB Press, 2020)
This study aims to compare reciprocal teaching styles influence, exercises and command on learning outcomes of pencak silat paleredan. Experimental research method with Pretest-Posttest Group Design research design. Samples that fulfilled the requirements were 38 people. The research found that 1) the influences of Teaching Style Reciprocal toward Learning Results Pencak Silat Tepak Paleredan, 2) There is the influence of Teaching Style Exercise on Learning Outcomes Pencak Silat Tepak Paleredan, 3) influences of Teaching Style Command on Learning Outcomes Pencak Silat Tepak Paleredan, 4) The teaching exercises style have more significant impact on learning outcomes martial test Tepak Paleredan compared Reciprocal teaching style and Command. Then it can be concluded that the three teaching styles have a significant influence on the learning outcomes of the Paleredan Pencak silat in the Universitas Nusa Cendana Penjaskesrek Academic Year 2019/2020